Genetic control of violacein biosynthesis to enable a pigment-based whole-cell lead biosensor. Issue 47 (28th July 2020) - Hui, Chang-ye; Guo, Yan; Liu, Lisa; Zhang, Nai-xing; Gao, Chao-xian; Yang, Xue-qin; Yi, Juan
Abstract : Genetically controlled violacein biosynthesis can enable a sensitive, visual, and qualitative biosensor for monitoring the presence of bioavailable lead. Abstract : Environmental risks continue to grow due to heavy metal contamination caused by anthropogenic activities. Accumulation of harmful quantities of lead poses a threat to aquatic organisms, plants, and human beings. Whole-cell biosensors, which can proliferate independently, can detect the bioavailable fraction to assess the effect of target heavy metal on the environmental ecosystem. In this study, the biosynthesis pathway of violacein was heterogeneously constructed under the control of the T7 lac promoter in E. coli . A dose–response relationship existed between the inducer and the production of violacein. The biosynthesis pathway of violacein was finally engineered under the regulation of Pb(ii )-dependent metalloregulator PbrR to assemble Pb(ii )-inducible whole-cell biosensor. It permitted specific biosensing of Pb(ii ) with extraordinary selectivity, and could resist the interferences from various metal ions. Color change by the intracellular accumulation of violacein could be recognized with the naked eye directly with high concentration of lead exposure, and quantified by determining the absorbance at 490 nm after butanol extraction. A good linear range for Pb(ii ) concentrations of 0.1875–1.5 μM was obtained. The novel pigment-based whole-cell biosensor could detect concentrations as low as 0.1875 μM Pb(ii ) based on in vitro quantification of violacein extracted by butanol, which is significantly lower than reported fluorescent protein-based PbrR-regulated biosensors based on direct measurement of whole cell fluorescence. These results indicate that genetically controlled violacein biosynthesis can enable a sensitive, visual, and qualitative biosensor for monitoring the presence of bioavailable Pb(ii ) in lead-contaminated water.